Biomass-based fiber composite material as well as preparation method and application thereof
By combining the fiber and silicon carbon material, the biomass base composite material is combined with the combination of the epidermis of the cypress rods and the silicon carbon material, which solves the environmental protection and health problems of existing car interior materials, and realizes high -performance automobile interior Preparation.
Patent Information
- Application Number
- CN202411672998.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-21
AI Technical Summary
The existing automotive interior parts are mainly made of plastic materials made of non-renewable resources, which have environmental problems and are harmful to human health.
The biomass -based fiber composite material is used to obtain cypress fibers by soaking the epidermis of cypress with sodium hydroxide solution, sodium silicate dehydration agent, sodium sulfate and sodium phosphate, and combined with silicon carbon material to add polypropylene materials to add polypropylene Resin and ethanol and other ingredients are made of fiber cloth through weaving processes.
This composite material has high -strength, humidity and hygroscopicness, insulation, sound insulation, and has the function of abrasion resistance, anti -static and eliminating odor, and is suitable for preparation of car interior parts.
Smart Images

Figure CN119371744A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and in particular to a biomass-based fiber composite material and a preparation method and application thereof. Background Art
[0002] With the continuous development of the automobile industry, environmental protection issues have become increasingly prominent, especially for materials inside the car that are in direct contact with drivers and passengers. In the existing technology, most interior decoration parts are made of plastic materials such as PVC, PS, and PP (i.e., polypropylene resin). Such industrial plastics are heavily dependent on non-renewable resources such as petroleum. They are not only not environmentally friendly, but the odors they emit often contain certain ingredients that are harmful to the human body. They do not meet regulatory requirements, and long-term contact will damage human health.
[0003] Based on the defects of the current automobile interior parts made of plastics such as PVC, PS, PP (i.e. polypropylene resin), it is necessary to improve them. Summary of the invention
[0004] In view of this, the present invention provides a biomass-based fiber composite material and application thereof to solve the defects existing in the prior art.
[0005] In a first aspect, the present invention provides a method for preparing a biomass-based fiber composite material, comprising the following steps:
[0006] Soak the cypress stem skin in a sodium hydroxide solution;
[0007] Add sodium silicate degumming agent to the soaked cypress stalk skin, and cook at 120-160℃ to decompose the colloid in the fiber;
[0008] Adding a solution containing sodium sulfite and composite sodium phosphate to the boiled flax stem skin to obtain flax fiber;
[0009] The ramie fiber is added into a bulking agent containing metal oxides and subjected to bulking and fluffing treatment at 35-60°C;
[0010] adding a qualitative agent to the expanded flax fiber;
[0011] Drying the qualitative cypress fiber;
[0012] The cypress stems are subjected to high temperature pyrolysis reaction to obtain silicon-carbon material;
[0013] Grinding the silicon-carbon material into powder to obtain carbon powder;
[0014] The carbon powder and the polypropylene resin are mixed, and then ethanol is added as a solvent, and polyacrylate is added as a dispersant, and stirred to obtain a slurry;
[0015] The slurry is coated on the surface of the dried cypress fiber, solidified, and spun into fiber strands;
[0016] The fiber raw yarn is woven into fiber cloth through a weaving process.
[0017] Preferably, the epidermis of the cypress stalks is soaked in a sodium hydroxide solution for 30 to 60 hours, wherein the mass concentration of the sodium hydroxide solution is 15 to 20 g / L.
[0018] Preferably, a sodium silicate degumming agent is added to the soaked cypress stalk skin, and in the step of steaming at 120-160° C., the steaming time is 4-8 hours, and the sodium silicate is added in the form of a sodium silicate solution, and the concentration of the sodium silicate solution is 2-4 g / L.
[0019] Preferably, a solution containing sodium sulfite and composite sodium phosphate is added to the boiled flax stem skin, and the mixture is allowed to stand for 20 to 30 hours to obtain flax fiber;
[0020] The preparation method of the solution containing sodium sulfite and compound sodium phosphate is as follows: sodium sulfite and compound sodium phosphate are added into water to obtain the solution containing sodium sulfite and compound sodium phosphate, wherein the concentration of sodium sulfite is 1-4 g / L and the concentration of compound sodium phosphate is 1-4 g / L.
[0021] Preferably, the fiber is added to a bulking agent containing a metal oxide and subjected to bulking and combing treatment at 35 to 60° C., and the bulking and combing treatment time is 2 to 3 hours; the bulking agent is prepared by adding MgO to water to obtain the bulking agent, wherein the concentration of MgO is 10 to 15 g / L.
[0022] Preferably, a qualitative agent is added to the expanded ramie fiber and treated at 25-30°C for 25-30 minutes, wherein the qualitative agent is prepared by adding CuCl2 into ammonia water to obtain a copper ammonia solution, which is the qualitative agent; the copper ion concentration in the copper ammonia solution is 0.5-1.5 mol / L.
[0023] Preferably, the cypress stalks are subjected to high temperature pyrolysis reaction to obtain the silicon-carbon material, which specifically comprises the following steps:
[0024] Pyrolyze cypress stems at 600-700°C for 2-4 hours under an inert atmosphere to obtain silicon-carbon material;
[0025] The inert atmosphere includes at least one of nitrogen, helium, neon and argon;
[0026] In the step of mixing carbon powder and polypropylene resin, the mass ratio of carbon powder to polypropylene resin is 1:(1-3), the mass ratio of carbon powder to solvent ethanol is 1:(38-42), and the mass ratio of carbon powder to dispersant polyacrylate is (40-42):1.
[0027] In a second aspect, the present invention further provides a biomass-based fiber composite material, which is prepared by the preparation method.
[0028] In a third aspect, the present invention further provides a biomass-based fiber composite material prepared by the preparation method or the use of the biomass-based fiber composite material in the preparation of automotive interior trims.
[0029] Preferably, a biomass-based fiber composite material is placed in a mold, and then a polypropylene resin is laid on the biomass-based fiber composite material, and then the biomass-based fiber composite material is laid on the polypropylene resin again, and the operation is repeated so that the biomass-based fiber composite material and the polypropylene resin are alternately arranged in sequence; then softened at a temperature of 200 to 220° C. for 3 to 7 minutes, and finally maintained at a pressure of 12.5 to 15 MPa for 60 to 80 seconds to obtain an automotive interior decoration part.
[0030] The biomass-based fiber composite material and its preparation method and application of the present invention have the following beneficial effects compared with the prior art:
[0031] The method of the biomass-based fiber composite material of the present invention can make full use of the high strength, moisture absorption and dehumidification, heat insulation, sound insulation and other properties of the ramie fiber by treating the ramie fiber material, and the silicon-carbon material made of ramie stems is mixed, dried and pressed. The composite material has wear resistance due to the carbon element, and also has the functions of anti-static and odor elimination. When the composite material prepared by the present invention is used as the lower baffle of the air-conditioning box in the car, the cross section of the ramie fiber under the electron microscope has a multi-level pore activated carbon material with micropores and macropores interconnected with each other. The porous feature has strong adsorption, and can quickly absorb and evaporate moisture, which is beneficial to keep the lower baffle in a dry state, and can also absorb the noise in the car. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0033] Figure 1 This is a SEM image of the slurry coated on the surface of dry ramie fiber in step S10 of Example 1 and cured at room temperature;
[0034] Figure 2 is a SEM image of the carbon powder prepared in step S8 of Example 1;
[0035] Figure 3This is a physical picture of an automobile interior decoration part (specifically, a lower baffle of an air-conditioning box) prepared by the preparation method of Example 1;
[0036] Figure 4 This is a SEM image of the ramie fiber in step S6 of Example 1;
[0037] Figure 5 This is a physical picture of the carbon powder prepared in step S8 of Example 1. DETAILED DESCRIPTION
[0038] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may be in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered ranges, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any cited numbers (fractions or integers) within the indicated range.
[0040] The present invention provides a method for preparing a biomass-based fiber composite material, comprising the following steps:
[0041] S1. Soak the epidermis of cypress stalks in a sodium hydroxide solution;
[0042] S2, adding sodium silicate degumming agent to the soaked cypress stalk skin, and cooking at 120-160°C to decompose the colloid in the fiber;
[0043] S3, adding a solution containing sodium sulfite and composite sodium phosphate to the boiled flax stem skin to obtain flax fiber;
[0044] S4, adding ramie fiber to a bulking agent containing metal oxides and subjecting the bulking fiber to a fluffing treatment at 35-60° C.;
[0045] S5, adding a qualitative agent to the expanded flax fiber;
[0046] S6, drying the qualitative cypress fiber;
[0047] S7, subjecting the cypress stems to high-temperature pyrolysis reaction to obtain silicon-carbon material;
[0048] S8, grinding the silicon-carbon material into powder to obtain carbon powder;
[0049] S9, mixing carbon powder and polypropylene resin, then adding ethanol as a solvent, and then adding polyacrylate as a dispersant, stirring to obtain slurry;
[0050] S10, coating the slurry on the surface of the dried ramie fiber, curing at room temperature, and weaving into fiber precursor;
[0051] S11, weaving the fiber raw yarn into fiber cloth through a weaving process.
[0052] In some embodiments, the epidermis of the cypress stalk is immersed in a sodium hydroxide solution (specifically, an aqueous sodium hydroxide solution) for 30 to 60 hours, and the mass concentration of the sodium hydroxide solution is 15 to 20 g / L.
[0053] In some embodiments, cypress stalks are taken, branches, leaves and surface impurities are removed, and the cypress stalk skin is cleaned and cut into 3 to 5 cm long pieces.
[0054] In some embodiments, sodium silicate degumming agent is added to the soaked cypress stalk skin, and in the step of steaming at 120-160° C., the steaming time is 4-8 hours; sodium silicate is added in the form of sodium silicate solution (aqueous solution), and the concentration of the sodium silicate solution is 2-4 g / L.
[0055] In some embodiments, a solution containing sodium sulfite and complex sodium phosphate is added to the boiled flax stem skin, and the solution is allowed to stand at room temperature (23±2° C.) for 20 to 30 hours to obtain flax fiber.
[0056] In some embodiments, the preparation method of the solution containing sodium sulfite and compound sodium phosphate is: adding sodium sulfite and compound sodium phosphate into water to obtain a solution containing sodium sulfite and compound sodium phosphate, wherein the concentration of sodium sulfite is 1 to 4 g / L, and the concentration of compound sodium phosphate is 1 to 4 g / L.
[0057] In some embodiments, the fiber is added to a bulking agent containing a metal oxide and subjected to a bulking and combing treatment at 35 to 60° C., and the bulking and combing treatment time is 2 to 3 hours. The bulking agent is prepared by adding MgO to water to obtain the bulking agent, wherein the concentration of MgO is 10 to 15 g / L.
[0058] In some embodiments, a qualitative agent is added to the expanded ramie fiber and treated at 25-30°C for 25-30 minutes, wherein the qualitative agent is prepared by adding CuCl2 into ammonia water to obtain a copper ammonia (Cu(NH3)4](OH)2) solution, which is the qualitative agent; the copper ion concentration in the copper ammonia solution is 0.5-1.5 mol / L.
[0059] In some embodiments, in the step of drying the qualitative flax fibers, the breaking strength of a single flax fiber is 5.2-6.9 cN / dtex (centinewtons per dtex, a unit of breaking strength, the maximum tensile force that a fiber can withstand), and the breaking elongation is 8-10%.
[0060] In some embodiments, cypress straw is subjected to high temperature pyrolysis reaction to obtain silicon-carbon material, which specifically includes the following steps:
[0061] Pyrolyze cypress stems at 600-700°C for 2-4 hours under an inert atmosphere to obtain silicon-carbon material;
[0062] The inert atmosphere includes at least one of nitrogen, helium, neon and argon.
[0063] In some embodiments, the silicon-carbon material is ground into powder to a particle size of 50 to 200 μm to obtain carbon powder.
[0064] The cypress stems are treated by high-temperature pyrolysis reaction in a gasification furnace to obtain silicon-carbon material. This material has a multi-level pore activated carbon material with micropores and macropores interconnected with each other. The porous characteristics have strong adsorption capacity, and it also has the functions of noise reduction and odor absorption.
[0065] In some embodiments, carbon powder and polypropylene resin are mixed, ethanol is added as a solvent, polyacrylate is added as a dispersant, and stirred to obtain a slurry;
[0066] Among them, in the step of mixing carbon powder and polypropylene resin, the mass ratio of carbon powder to polypropylene resin is 1:(1-3), the mass ratio of carbon powder to solvent ethanol is 1:(38-42), and the mass ratio of carbon powder to dispersant polyacrylate is (40-42):1.
[0067] In some embodiments, the fiber raw yarn is woven into a fiber cloth through a weaving process, wherein the density of the fiber cloth is 0.7-1.1 g / cm 3 ; The thickness of the fiber cloth is 6 to 10 mm.
[0068] In some embodiments, the weaving process of the fiber cloth is such that every two directions are either parallel or cross-angled, that is, the fiber raw filaments are woven through warp and weft to obtain the fiber cloth.
[0069] Based on the same inventive concept, the present invention also provides a biomass-based fiber composite material, which is prepared by the above-mentioned preparation method.
[0070] Based on the same inventive concept, the present invention also provides a biomass-based fiber composite material prepared by the above-mentioned preparation method or the use of the above-mentioned biomass-based fiber composite material in the preparation of automobile interior decoration parts.
[0071] The specific automobile interior decoration part can be the lower baffle of the air-conditioning box in the automobile.
[0072] In some embodiments, a biomass-based fiber composite material is placed in a mold, and then a polypropylene resin is laid on the biomass-based fiber composite material, and then the biomass-based fiber composite material is laid on the polypropylene resin again, and the operation is repeated so that the biomass-based fiber composite material and the polypropylene resin are alternately arranged in sequence; then softened at a temperature of 200 to 220°C for 3 to 7 minutes, and finally maintained at a pressure of 12.5 to 15 MPa for 60 to 80 seconds to obtain automotive interior parts.
[0073] Specifically, the mass ratio of the biomass-based fiber composite material to the polypropylene resin is (4-6): (4-6), and the biomass-based fiber composite material and the polypropylene resin are alternately arranged in sequence until the final product meets the surface density requirement (600g / m 2 ~1800g / m 2 ), then softened at a temperature of 200-220°C for 3-7 minutes, and finally maintained at a pressure of 12.5-15 MPa for 60-80 seconds to obtain automotive interior parts.
[0074] In some embodiments, the automotive interior decoration parts prepared by the present invention can also have the effects of cypress and hemp on strengthening the spleen and replenishing qi, dispelling wind and dampness, etc.
[0075] The present invention uses biomass-based fiber composite materials to prepare automotive interior decoration parts, such as the lower baffle of the air-conditioning box in the car. Under the electron microscope, the cross section of the cypress fiber has micropores and macropores interconnected in a multi-level channel activated carbon material. The porous characteristics have strong adsorption, and can quickly absorb and evaporate water. The use of biomass-based fiber composite materials to prepare the lower baffle of the air-conditioning box is conducive to keeping the lower baffle in a dry state, and can also absorb the noise in the car. In addition, the product also has a light Chinese medicine fragrance.
[0076] The ramie fiber material obtained after treatment in the present invention can make full use of the high strength, moisture absorption and discharge, heat insulation, sound insulation and other properties of the ramie fiber, and is mixed and dried with the silicon-carbon material made of ramie stems to finally prepare a biomass-based fiber composite material. The biomass-based fiber composite material has wear resistance due to the carbon element it contains, and also has the functions of anti-static and odor elimination.
[0077] The following further illustrates the biomass-based fiber composite material of the present application and its preparation method and application with specific examples. This section further illustrates the content of the present invention in conjunction with specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0078] Example 1
[0079] The present invention provides a method for preparing a biomass-based fiber composite material, comprising the following steps:
[0080] S1. Take cypress stalks, remove branches, leaves and surface impurities, and clean the cypress stalk skin, then cut it into 3-5 cm lengths; soak the cypress stalk skin in a 20 g / L sodium hydroxide aqueous solution for 50 h;
[0081] S2. Adding sodium silicate degumming agent to the soaked cypress stalk skin, cooking at 140°C for 6 hours to decompose the colloid in the fiber; sodium silicate is added in the form of sodium silicate solution (aqueous solution), and the concentration of the sodium silicate solution is 3g / L;
[0082] S3. Adding a solution containing sodium sulfite and compound sodium phosphate to the boiled flax stem skin, and standing at room temperature (25° C.) for 24 hours to obtain flax fiber; the preparation method of the solution containing sodium sulfite and compound sodium phosphate is as follows: adding sodium sulfite and compound sodium phosphate to water to obtain a solution containing sodium sulfite and compound sodium phosphate, wherein the concentration of sodium sulfite is 2 g / L and the concentration of compound sodium phosphate is 3 g / L;
[0083] S4, adding ramie fiber to a bulking agent containing metal oxides and bulking and combing the fiber at 45° C. for 2 hours; the bulking agent is prepared by adding MgO to water to obtain the bulking agent, wherein the concentration of MgO is 12 g / L;
[0084] S5. Add a qualitative agent to the expanded ramie fiber and treat it at 30° C. for 30 min. The qualitative agent is prepared by adding CuCl2 to ammonia water to obtain a copper ammonia (Cu(NH3)4](OH)2) solution, which is the qualitative agent. The copper ion concentration in the copper ammonia solution is 1 mol / L.
[0085] S6, drying the qualitative cypress fiber at room temperature;
[0086] S7, pyrolyzing the cypress stems at 650° C. for 3 h under a nitrogen atmosphere to obtain a silicon-carbon material;
[0087] S8, grinding the silicon-carbon material into powder so that the particle size is 100 μm to obtain carbon powder;
[0088] S9, mixing carbon powder and polypropylene resin in a mass ratio of 1:2, then adding ethanol as a solvent, and then adding polyacrylate as a dispersant, stirring to obtain a slurry; the mass ratio of carbon powder to solvent ethanol is 1:40, and the mass ratio of carbon powder to dispersant polyacrylate is 40:1;
[0089] S10, coating the slurry on the surface of the dried ramie fiber, curing at room temperature, and weaving into fiber precursor;
[0090] S11, weaving the fiber raw yarn into fiber cloth through a weaving process.
[0091] This embodiment also provides an application of the biomass-based fiber composite material prepared in Example 1 in preparing automobile interior decoration parts. Specifically, the preparation method of the automobile interior decoration parts includes:
[0092] The biomass-based fiber composite material is placed in a mold, and then a polypropylene resin is laid on the biomass-based fiber composite material, and then the biomass-based fiber composite material is laid on the polypropylene resin again, and the operation is repeated to make the biomass-based fiber composite material and the polypropylene resin alternately arranged in sequence; then softened at a temperature of 220°C for 5 minutes, and finally maintained at a pressure of 15MPa for 80 seconds to obtain an automotive interior decoration part; wherein the mass ratio of the biomass-based fiber composite material to the polypropylene resin is 5:5, and the biomass-based fiber composite material and the polypropylene resin are alternately arranged in sequence until the final product meets the surface density requirement (1200g / m 2 ).
[0093] Performance Characterization
[0094] Figure 1 This is a SEM picture of the slurry coated on the surface of dry ramie fiber in step S10 of Example 1 and cured at room temperature.
[0095] from Figure 1 It can be seen that the carbon powder is adsorbed on the surface of the cypress fiber, and eventually large pieces (particle size> 10μm) of honeycomb solid are deposited on the fiber surface. The composite material uses cypress fiber as the matrix, supplemented by the modification of silicon-carbon particles (for reinforcement), which is beneficial to the improvement of the mechanical properties, wear resistance and antistatic properties of the fiber (high carbon content can improve the stiffness and hardness of the fiber, and carbon powder is a highly conductive powder material, which is beneficial to reduce surface impedance and improve antistatic ability). At the same time, the microporous structure of the carbon powder has pore adsorption, which can improve the quality of odor and sound absorption.
[0096] Figure 2 This is a SEM image of the carbon powder prepared in step S8 of Example 1.
[0097] from Figure 2It can be seen that the prepared carbon powder is a porous material with scaly protrusions and tiny pores on the surface. These structures can greatly increase the specific surface area of the material, thereby improving its ability to adsorb sound and odor.
[0098] Figure 3 This is a physical picture of an automobile interior decoration part (specifically, a lower baffle of an air-conditioning box) prepared by the preparation method of Example 1.
[0099] Figure 4 This is the SEM image of the ramie fiber in step S6 of Example 1.
[0100] Figure 5 This is a physical picture of the carbon powder prepared in step S8 of Example 1.
[0101] The Shore hardness of the automobile interior parts prepared in Example 1 is 65, while the Shore hardness of automobile interior parts prepared by conventional polypropylene resin is 40-50; the surface impedance value of the automobile interior parts prepared in Example 1 is 1.2×10 10 Ω, while the surface impedance of traditional automotive interior parts made of polypropylene resin is >10 16 Ω; The above shows that the automotive interior parts prepared by the present invention have better wear resistance and antistatic properties (the charge of the material with low surface resistance can easily flow on the surface, so it is not easy to accumulate and generate static electricity).
[0102] The automotive interior parts prepared in Example 1 have a strong plant fiber fragrance (Chinese medicine fragrance) and a TVOC value of 765 μg / m 3 The traditional automotive interior parts made of polypropylene resin have a strong plastic smell and a TVOC value of 16273μg / m 3 ,, indicating that the automotive interior parts prepared by the present invention can eliminate odor. TVOC refers to total organic volatiles, which is a quantitative indicator of automobile air pollution. It mainly includes small molecular volatiles such as benzene, alkanes, and aromatic hydrocarbons. The larger the TVOC value, the larger the odor molecules entering the human respiratory system and the worse the odor. For passenger car interior parts, TVOC is generally required to be less than 15000μg / m 3 The automobile interior decoration parts prepared by the present invention have a lower TVOC value, are more environmentally friendly and less harmful to the human body.
[0103] The automotive interior trim prepared in Example 1 has a bending strength of up to 50.3 MPa and a bending modulus of up to 3798 MPa, and has good mechanical properties.
[0104] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a biomass-based fiber composite material, characterized in that: The following steps are involved: Soak the cypress stem skin in a sodium hydroxide solution; Add sodium silicate degumming agent to the soaked cypress stalk skin, and cook at 120-160℃ to decompose the colloid in the fiber; Adding a solution containing sodium sulfite and composite sodium phosphate to the boiled flax stem skin to obtain flax fiber; The ramie fiber is added into a bulking agent containing metal oxides and subjected to bulking and fluffing treatment at 35-60°C; Adding a qualitative agent to the expanded flax fiber; Drying the qualitative cypress fiber; The cypress stems are subjected to high temperature pyrolysis reaction to obtain silicon-carbon material; Grinding the silicon-carbon material into powder to obtain carbon powder; The carbon powder and the polypropylene resin are mixed, and then ethanol is added as a solvent, and polyacrylate is added as a dispersant, and stirred to obtain a slurry; The slurry is coated on the surface of the dried cypress fiber, solidified, and spun into fiber strands; The fiber raw yarn is woven into fiber cloth through a weaving process.
2. The method for preparing a biomass-based fiber composite material according to claim 1, characterized in that: The epidermis of the cypress stalks is soaked in a sodium hydroxide solution for 30 to 60 hours, wherein the mass concentration of the sodium hydroxide solution is 15 to 20 g / L.
3. The method for preparing a biomass-based fiber composite material according to claim 1, characterized in that: A sodium silicate degumming agent is added to the soaked cypress stalk skin, and the mixture is steamed at 120-160° C. for 4-8 hours. The sodium silicate is added in the form of a sodium silicate solution with a concentration of 2-4 g / L.
4. The method for preparing a biomass-based fiber composite material according to claim 1, characterized in that: Adding a solution containing sodium sulfite and complex sodium phosphate to the boiled flax stem skin, and leaving it to stand for 20 to 30 hours, thereby obtaining flax fiber; The preparation method of the solution containing sodium sulfite and compound sodium phosphate is as follows: sodium sulfite and compound sodium phosphate are added into water to obtain the solution containing sodium sulfite and compound sodium phosphate, wherein the concentration of sodium sulfite is 1-4 g / L and the concentration of compound sodium phosphate is 1-4 g / L.
5. The method for preparing a biomass-based fiber composite material according to claim 1, characterized in that: The fiber is added to a bulking agent containing a metal oxide and subjected to bulking and combing treatment at 35 to 60° C. The bulking and combing treatment time is 2 to 3 hours. The bulking agent is prepared by adding MgO to water to obtain the bulking agent, wherein the concentration of MgO is 10 to 15 g / L.
6. The method for preparing a biomass-based fiber composite material according to claim 1, characterized in that: A qualitative agent is added to the expanded ramie fiber and treated at 25-30° C. for 25-30 minutes, wherein the qualitative agent is prepared by adding CuCl2 into ammonia water to obtain a copper ammonia solution, which is the qualitative agent; the copper ion concentration in the copper ammonia solution is 0.5-1.5 mol / L.
7. The method for preparing a biomass-based fiber composite material according to claim 1, characterized in that: The cypress stems are subjected to high temperature pyrolysis reaction to obtain silicon-carbon material, which specifically comprises the following steps: Pyrolyze cypress stems at 600-700°C for 2-4 hours under an inert atmosphere to obtain silicon-carbon material; The inert atmosphere includes at least one of nitrogen, helium, neon and argon; In the step of mixing carbon powder and polypropylene resin, the mass ratio of carbon powder to polypropylene resin is 1:(1-3), the mass ratio of carbon powder to solvent ethanol is 1:(38-42), and the mass ratio of carbon powder to dispersant polyacrylate is (40-42):
1.
8. A biomass-based fiber composite material, characterized in that: The preparation method is as described in any one of claims 1 to 7.
9. Use of the biomass-based fiber composite material prepared by the preparation method according to any one of claims 1 to 7 or the biomass-based fiber composite material according to claim 8 in the preparation of automotive interior trims.
10. The use as claimed in claim 9, wherein the biomass-based fiber composite material is placed in a mold, and then a polypropylene resin is laid on the biomass-based fiber composite material, and then the biomass-based fiber composite material is laid on the polypropylene resin again, and the operation is repeated so that the biomass-based fiber composite material and the polypropylene resin are alternately arranged in sequence; then softened at a temperature of 200 to 220° C. for 3 to 7 minutes, and finally maintained at a pressure of 12.5 to 15 MPa for 60 to 80 seconds to obtain an automotive interior component.
Citation Information
Patent Citations
Hemp degumming and softening synchronous treatment process
CN102330158A
Automobile composite material prepared by taking bamboo fibers as main reinforcement, and preparation method of automobile composite material
CN108384107A
Natural fiber reinforced porous composite material
CN114316438A
Continuous fiber reinforced composite material and preparation method thereof
CN118325283A